Choice Bracketing and Environmental Policy: A Behavioral Economics Perspective on Influencing Decisions for Sustainable Consumption - Amirah Ulfah (Winaya Inspirasi Nusantara Foundation, 2026)
Environmental challenges are increasingly shaped by individual decision making which consist of small and repeated choices whose cumulative impacts are often overlooked. Despite rising public awareness, a persistent gap remains between knowledge and actual behavior, indicating limitations in policy approaches based on rational choice assumptions. This study aims to examine how choice bracketing, a concept from behavioral economics, can be used as an analytical framework to better understand environmental behavior and inform environmental policy design. The study employs a narrative literature review drawing on peer reviewed journal articles in behavioral economics, environmental economics, and environmental policy. The analysis synthesizes theoretical and empirical studies that examine how individuals evaluate decisions, perceive risk, and respond to policy interventions in environmental contexts. The findings reveal three key patterns. First, environmental behavior is frequently shaped by narrow bracketing, as individuals tend to evaluate small and repetitive decisions separately, leading to underestimation of cumulative and long-term impacts. Second, many existing policy interventions implicitly operate through broad bracketing by providing aggregate information, framing cumulative risks, or emphasizing long term economic consequences. Third, narrow bracketing is not inherently detrimental, as heuristics and narrow goal setting can reduce cognitive load and support consistent behavior under complex decision environments. These findings highlight the importance of aligning policy design with how individuals evaluate decisions. By positioning choice bracketing as a unifying mechanism, this study contributes to behavioral economics by offering an integrated perspective on environmental decision making and identifying flexible policy pathways for promoting sustainable behavior.